(untitled) (Conferencea, 2023)
Formation of H2O2 free radicals as a result of lipid peroxide oxidation (LPO) in the membrane is of great importance in pathological processes. Increased production of free radicals in the mitochondrial respiratory complex weakens the antioxidant defense system and damages membrane lipoprotein components. In toxic hepatitis caused by tetrachloromethane (CCl4) and many other pathologies, the intensity of LPO increases based on the development of oxidative stress. In conditions of CCl4-induced toxic hepatitis, biologically active substances are widely used to reduce membrane LPO [1; 2].